Review. Issue 1 (1st March 2014) - Fuchs, Mathias
Games people play The Video Game Industry: Formation, Present State, and Future, Peter Zackariasson and Timothy Wilson (eds) (2012) New York: Routledge, 282 pp., ISBN: 9780415896528, h/bk, £85.00 (GBP)